2020
DOI: 10.3389/fonc.2020.00491
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer Activity of Centipeda minima Extract in Triple Negative Breast Cancer via Inhibition of AKT, NF-κB, and STAT3 Signaling Pathways

Abstract: Breast cancer is the most commonly diagnosed cancer in females worldwide. Estimates from the World Health Organization (WHO) International Agency for Research on Cancer, suggest that globally, there were around 2.1 million new breast cancer cases and 627,000 deaths due to breast cancer in 2018. Among the subtypes of breast cancer, triple negative breast cancer (TNBC) is the most aggressive and carries the poorest prognosis, largest recurrence, and lowest survival rate. Major treatment options for TNBC patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 70 publications
1
27
0
Order By: Relevance
“…Preparation of CME was conducted as described previously ( Chan et al, 2016 ; Lee et al, 2020 ). In brief, CM was air-dried and ground to a coarse powder.…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of CME was conducted as described previously ( Chan et al, 2016 ; Lee et al, 2020 ). In brief, CM was air-dried and ground to a coarse powder.…”
Section: Methodsmentioning
confidence: 99%
“…Especially, CS reduced the tumor area and nodules that spread to lung and liver by suppressing MMP-2 and MMP-9 [ 114 ]. Lee et al demonstrated that Centipeda minima ethanol extract (CME) significantly reduced cancer cell viability and suppressed cancer cell migration via AKT, NF-κB, and STAT3 signaling pathways [ 115 ]. Park et al presented that Cirsium japonicum var.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, there were some studies conducting experiments both on in vivo and in vitro. Since the results showed the difference between cell models and animal models, it is necessary to conduct further research and discussion about how the difference occurred [ 115 , 129 ]. In other words, some studies on bio-systemic mechanisms and interactions of herbal medicine are demanded.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 2.1 million people will be diagnosed with breast cancer in 2018, effectively making the ever-growing breast cancer population even larger ( Ferlay et al, 2018 ). Breast cancer is a heterogeneous disease that can be caused by many signaling pathways that are responsible for cell proliferation and cell apoptosis, such as PI3K/AKT/mTOR, JAK/STAT, PTEN/AKT/MDM2/p53, and AKT/NF-κB signaling pathway ( Wan et al, 2019 ; Lee et al, 2020 ; Martínez-Rodríguez et al, 2020 ; Narayanankutty, 2020 ; Nunnery and Mayer, 2020 ). Subsequently, due to genetic variability, different breast patients often exhibit varied susceptibility to different signaling pathways.…”
Section: Discussionmentioning
confidence: 99%